2022
DOI: 10.1111/bjh.18060
|View full text |Cite
|
Sign up to set email alerts
|

Oral anti‐coagulant treatment patterns in atrial fibrillation patients diagnosed with cancer: A Danish nationwide cohort study

Abstract: Data on the use of oral anti‐coagulants (OAC) for stroke prevention in cancer patients with atrial fibrillation (AF) are sparse. Nationwide cohort study of patients with AF (2012–2018) and an indication for OAC who were diagnosed with cancer at least one year later (N = 12 756). We identified treatment with OAC at cancer diagnosis and the following year and described the incidence of discontinuing or switching between warfarin and direct oral anti‐coagulants (DOACs). We also described baseline characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
2
0
0
Order By: Relevance
“…In addition to dosing frequency, other predictors of impaired adherence include older age and relevant comorbidities, mainly congestive heart failure, dementia, and metastatic cancer. Older age, dementia, and metastatic cancer are consistent with results from previous studies of other OACs [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…In addition to dosing frequency, other predictors of impaired adherence include older age and relevant comorbidities, mainly congestive heart failure, dementia, and metastatic cancer. Older age, dementia, and metastatic cancer are consistent with results from previous studies of other OACs [35,36].…”
Section: Discussionsupporting
confidence: 90%
“…3 More recent studies and studies evaluating patients with VTE reported nonpersistent rates varying from 5 to 60% during a follow-up period between 2 months and 4 years. 4,5,8,10,[21][22][23][24][25] The persistence rate of the current study fits in this variation of DOAC nonpersistence. In the previous studies, lower persistence rates were seen in patients with a longer follow-up period, in anticoagulant-naïve patients and in patients treated with dabigatran.…”
Section: Doac Nonpersistencesupporting
confidence: 73%